Digital versus conventional techniques for construction of mandibular implant retained overdenture - Abd Elsalam Awad Ali; Ahmed Habib; Mohamed Shady (BMC Oral Health)
Abstract Background This study aimed to evaluate two different construction techniques (conventional and 3D-printed techniques) for two implant-retained complete mandibular overdentures regarding mechanical wear of the occlusal surface using 3D digital analysis and occlusion force distribution using the digital occlusal analysis system (Occlusense). Methods Twenty patients were selected for this study from the prosthetic department, Faculty of Dentistry, Mansoura University. Each patient received two implants in the mandibular canine areas with locator attachments to retain the overdentures. According to the overdenture construction technique, all patients were randomly divided into two equal groups: the conventional heat polymerized overdenture group and the 3D-printed overdenture group. The mandibular overdentures were compared and evaluated immediately and after 12 months of insertion regarding mechanical wear of the occlusal surface using 3D digital analysis and occlusal force distribution using a digital occlusal analysis system (Occlusense). Results 3d printed group showed significantly higher occlusal surface wear than conventional group after twelve months (T12) with a p value ≤ 0.05. 3d printed group showed significantly more occlusal force distribution than conventional group with a p value ≤ 0.05. Also, there was a significant difference in occlusal force distribution with advance of time for each group, with a p value ≤ 0.05 level of significance. Conclusion Within the limitations of this study, it was shown that implant overdentures constructed by 3D-printing techniques offer a promising results in distribution of occlusal forces for achieving occlusal equilibration. However, in term of wear resistance more developments need to be done to improve material properties. Trial registration The study was approved by the local ethical committee of the Faculty of Dentistry, Mansoura University (No. A02060922) (6/9/2022) and retrospectively registered at ClinicalTrials.gov (ClinicalTrials.gov Identifier NCT06139003) (16/11/2023).